2022
DOI: 10.1007/s00170-022-10340-x
|View full text |Cite
|
Sign up to set email alerts
|

Weld morphology, microstructure evolution, and mechanical properties of laser beam welding of wire arc additive manufactured Al-Cu substrate

Abstract: Additive manufacturing (AM) cannot meet the manufacturing requirements of speci c large structures, so use the welding method to joint the small size parts of AM to solve the problem. In work, the laser weld 3mm thick samples cut from WAAM block under different laser powers and welding directions to explore the feasibility of technology. The properties evolution, and weldability of the laser-welded wire arc additive manufactured Al-Cu alloy joints are investigated. The results indicate that the wire arc additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…As mentioned before, to the best knowledge of the authors, there is only one study evaluating the weldability of Al parts manufactured by WAAM. In this study, Shi et al [41] observed the good weldability of WAAM-manufactured 2319 Al alloy, by realising a nearly-free of defects LBW joint. The microstructures of the laser-welded joint consisted of columnar and fine equiaxed grains.…”
Section: Fusion Welding Processesmentioning
confidence: 63%
See 3 more Smart Citations
“…As mentioned before, to the best knowledge of the authors, there is only one study evaluating the weldability of Al parts manufactured by WAAM. In this study, Shi et al [41] observed the good weldability of WAAM-manufactured 2319 Al alloy, by realising a nearly-free of defects LBW joint. The microstructures of the laser-welded joint consisted of columnar and fine equiaxed grains.…”
Section: Fusion Welding Processesmentioning
confidence: 63%
“…Several researchers have evaluated the use of the LBW process alone for additive-manufactured Al alloys [36,[38][39][40][41][42][43][44][45][46][47][48][49][50]. The general and consistent results that porosity is the main defect in these welds [36,[38][39][40][41][42][43][44][45][46][47][48][49][50]. According to Emmelm [38], pores are formed during the welding process of aluminium alloys by a known as heterogeneous nucleation.…”
Section: Fusion Welding Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the compressive stress on the welding tool was at the back side and the tensile stress on the welding tool was at the front side. Shi et al [ 10 ] employed laser welding to join the additive manufactured parts. The results indicated that the weld joint of the Al–Cu alloy was nearly free of defects.…”
Section: Introductionmentioning
confidence: 99%